2017
DOI: 10.1051/e3sconf/20171402031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis on research results of FGD gypsum briquetting

Abstract: Abstract. FGD gypsum products can be characterized by significant solubility in water and dusting in dry state. These characteristics can cause a considerable pollution of air, water and soil. Among many approaches of preparing utilization of this waste, the process of compaction using briquetting has proved to be very effective. Using FGD gypsum products a new material of fertilizers characteristics has been acquired and this material is resistant to the conditions of transportation. This paper presents resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The fuels prepared in a mixer were then placed in a roll press equipped with a gravity feeder and forming rings allowing for obtaining a saddle-shaped briquettes of 6.5 cm 3 volume. Studies conducted in the Department of Manufacturing Systems confirmed the efficiency of using this type of asymmetrical layout compacting system for briquetting waste materials [7,8,9,10]. The amount of fine-grained solid fuels was 5 -7 kg.…”
Section: Methodsmentioning
confidence: 83%
“…The fuels prepared in a mixer were then placed in a roll press equipped with a gravity feeder and forming rings allowing for obtaining a saddle-shaped briquettes of 6.5 cm 3 volume. Studies conducted in the Department of Manufacturing Systems confirmed the efficiency of using this type of asymmetrical layout compacting system for briquetting waste materials [7,8,9,10]. The amount of fine-grained solid fuels was 5 -7 kg.…”
Section: Methodsmentioning
confidence: 83%
“…Huge amounts of gypsum are being produced through flue-gas desulfurization (FGD) processes, which remove sulfur dioxide (SO 2 ) from exhaust flue gases (as a requirement from regulatory authorities to reduce release of SO 2 into the atmosphere) from coal-fired power plants. Kosturkiewicz et al (2017) have provided a detailed account of gypsum-based products through the FGD process. It is to be noted that, as the world is moving towards sustainable solutions and replacing unsustainable energy sources (including coal-fired power generation) with sustainable sources, future generation of such gypsum through FGD is likely to be reduced.…”
Section: Introductionmentioning
confidence: 99%